GENETIC CHARACTER OF Tacca chantrieri André AND THEIR PHYLOGENETIC INFERENCE IN THE GENUS Tacca BASED ON ITS-rDNA SEQUENCES ANALYSIS - Dinh Giap, Vu; Mai Phuong, Pham; Thi Tuyet Xuan, Bui; Van Thang, Bui; Thi Thuy Linh, Trinh; Kim Dung, Vu; Dinh Duy, Vu (Journal of Forestry Science and Technology, 2021)
Tacca J.R. & G. Forst is the only genus in Taccaceae includes 17 species distributed on the world, of which have found 7 species in Vietnam. DNA barcoding is a method of rapid species identification and discovery using short, standardized genes or DNA regions. In this study, we have sequences nuclear gene region (ITS-rDNA) from 9 individuals of Tacca chantrieri André belonging to three natural populations (Song Hinh Nature Reserve, Phu Yen Province; Cuc Phuong National Park, Ninh Binh province and Ba Vi National Park, Ha Noi city) to investigate genetic character and their phylogenetic inference in the genus Tacca. DNA was extracted from the tissue of leaves. The nucleotide sequence of ITS-rDNA was determined to be 674bp. All samples collected at three different geographic locations for the ITS-rDNA gene regions showed that their length and nucleotide sequence similarity were 100%. The analysis indicated the mean base compositions were nucleotide T(U) (16.9%), C (29.5%), A (20.3%) and G (33.2%). The TA content was found to be low (37.2%), compared to 62.8% of the CG content. Phylogenetic analyses using maximum likelihood (ML) indicated that all samples from Vietnam have a close relationship with Tacca chantrieri in GenBank with strong supporting values (99%). Genetic p-distances interspecific divergence within and among Tacca species were varied from 0% to 19%, mean genetic distance 10%. The gene (ITS-rDNA) is used as a barcode in the identification of the Tacca species in Vietnam.